2017
DOI: 10.1097/nmd.0000000000000685
|View full text |Cite
|
Sign up to set email alerts
|

The Comorbidity of Daydreaming Disorder (Maladaptive Daydreaming)

Abstract: To determine the comorbidity profile of individuals meeting criteria for a proposed new disorder, daydreaming disorder (more commonly known as maladaptive daydreaming [MD]), the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) and the Structured Clinical Interview for DSM-IV Dissociative Disorders were administered to 39 participants who met criteria for MD on a structured interview. We determined high rates of comorbidity: 74.4% met criteria for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 14 publications
9
100
1
5
Order By: Relevance
“…Examining the characteristics of the sample, our data suggested that this was more of a clinical than a non-clinical sample; 87% were above the clinical cutoff for suspected MD, over two thirds of the sample had been in therapy at least once in their lives, and over half of the sample reported having received at least one psychiatric diagnosis. This finding is in accordance with previous research suggesting that MD is characterized by high levels of concomitant psychopathology ( 30 ). On average, as a group, on their first assessment participants reported spending 4.5 h actively engaging in daydreaming on that single day, suggesting that their MD was indeed time-consuming and excessive, taking up over a quarter of their waking time.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Examining the characteristics of the sample, our data suggested that this was more of a clinical than a non-clinical sample; 87% were above the clinical cutoff for suspected MD, over two thirds of the sample had been in therapy at least once in their lives, and over half of the sample reported having received at least one psychiatric diagnosis. This finding is in accordance with previous research suggesting that MD is characterized by high levels of concomitant psychopathology ( 30 ). On average, as a group, on their first assessment participants reported spending 4.5 h actively engaging in daydreaming on that single day, suggesting that their MD was indeed time-consuming and excessive, taking up over a quarter of their waking time.…”
Section: Discussionsupporting
confidence: 94%
“…Notably, despite the finding that obsessive-compulsive symptoms are a central mechanism in the daily dynamics of MD, only a small subset of our sample reported having a diagnosis of OCD (5 participants, which amounts to only 6.49% of the sample). This discrepancy suggests that obsessive-compulsive symptoms and MD share common mechanisms and interact with each other on one hand, but MD does not seem to be merely a subtype of OCD on the other hand [also see ( 30 )]. Many individuals with MD report that they are constantly drawn to daydreaming in a compulsory fashion, and have difficulty controlling their thoughts ( 26 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, an ongoing debate discusses that MW may be a heterogeneous construct and that different definitions of MW should be seen as complementary rather than competing (Seli et al , ). For instance, daydreaming is often considered as a part of MW and is in its extreme form referred to as maladaptive daydreaming, which overlaps to a high degree with ADHD (Somer, Soffer‐Dudek, & Ross, ). As such, future studies should address this overlap and differentiation between MW, ADHD and maladaptive daydreaming.…”
Section: Discussionmentioning
confidence: 99%